Meat pies : an emerging American craft - Polcyn, Brian; Ruhlman, Michael, 1963- (W. W. Norton & Company, 2024)
Chef Brian Polycn and Michael Ruhlman, authors of the landmark cookbook Charcuterie, reunite to teach home cooks and professional chefs the craft of savory pies with 90 new recipes and step-by-step how-to photographs. Learn the secrets of a good dough, explore classic meat preparations, and discover how fish and vegetable pie traditions can be adapted for today's tastes.